Experimental Investigation on Hydraulic Fracture Morphology of Inter-Salt Shale Formation - Zhang, Xiaoyu; Bi, Zhenhui; Chang, Xin; Wang, Lei; Yang, Hanzhi (Frontiers in Energy Research, 2021)
The inter-salt shale in the Qianjiang formation of Jianghan Basin in China is characterized by multiple salt-shale bedding planes, various rock strength, and high heterogeneity of rock mechanics. In this paper fracturing experiments under different conditions were carried out to study the effects of the injection velocity, type of fracturing fluid and interface strength on the propagation law of hydraulic fracture in the salt sedimentary rhythm there. In the meantime, Acoustic emission (AE) system and radial strain sensor were applied to monitor experimental process. The result indicate that (1) compared with the shale, there are four fracture propagation modes mainly being observed: passivating type (Mode I), “I”-type (Mode II), penetration type (Mode III) and mixed type ( (Mode IV)), among which the mixed type is the relatively complex crack propagation mode.(2)With the increase of injection rate and viscosity of fracturing fluid, the hydraulic fracture will penetrate cementation surface more easily. (3)The increase of flow rate and viscosity will increase the breakdown pressure. The breakdown pressure of high strength cementation surface is 16.70% higher than that of low strength.